A Cross-Sectional Study of Treatments for Behavioral Disorders Following Traumatic Brain Injury: Comparison With French Recommendations. Issue 4 (July 2019) - Bourseau, Tiphaine; Saoût, Virginie; Ali, Pauline; Pouliquen-Loriferne, Uriell; Allain, Philippe; Dinomais, Mickaël
Abstract : Objective: To give a cross-sectional overview of ongoing management of behavioral disorders following traumatic brain injury (TBI) in a region of France, to compare this with recent recommendations from the French Society of Physical Medicine and Rehabilitation (SOFMER), and to evaluate associations between treatments and participant characteristics. Setting: Outpatients referred to medical or community-based facilities in a region of France. Participants: One hundred twenty-nine adults with moderate to severe TBI, in the postacute period (over 3 months postinjury). Design: Cross-sectional cohort study. Main Measures: Sociodemographic data, ongoing interventions including psychotherapy and medication, behavioral disorders assessed by the Behavioral Dysexecutive Syndrome Inventory (BDSI). Results: Thirty-three percent of participants received ongoing psychotherapy and 43% were on medication. The most prescribed medications were antidepressants (21%), neuroleptics (18%), anxiolytics (16%), and mood stabilizers (14%). Eighty-five participants (71%) presented a current Behavioral Dysexecutive Syndrome (BDS) according to the BDSI. These participants more frequently received treatment ( P = .004), psychotherapy ( P = .048), medications (often 2 or more) ( P = .007), and particularly antiepileptic mood stabilizers ( P = .037) compared with those without BDS. Conclusion: Although recommended as first-line treatment, few participants with BDS received psychotherapy. Medications were overused, especially neuroleptics in view of their potential adverse effects. In contrast, recommended medications, such as mood stabilizers and β-blockers, did not appear to be highly prescribed whatever the evolution. Compliance with recommendations seemed insufficient.